Selected modern methods and tools for public participation in urban planning – a review - Haklay, Muki; Jankowski, Piotr; Zwoliński, Zbigniew (Quaestiones Geographicae, 2018)
The paper presents a review of contributions to the scientific discussion on modern methods and tools for public participation in urban planning. This discussion took place in Obrzycko near Poznań, Poland. The meeting was designed to allow for an ample discussion on the themes of public participatory geographic information systems, participatory geographic information systems, volunteered geographic information, citizen science, Geoweb, geographical information and communication technology, Geo-Citizen participation, geo-questionnaire, geo-discussion, GeoParticipation, Geodesign, Big Data and urban planning. Participants in the discussion were scholars from Austria, Brazil, the Czech Republic, Finland, Ireland, Italy, the Netherlands, Poland, the United Kingdom, and the USA. A review of public participation in urban planning shows new developments in concepts and methods rooted in geography, landscape architecture, psychology, and sociology, accompanied by progress in geoinformation and communication technologies. The discussions emphasized that it is extremely important to state the conditions of symmetric cooperation between city authorities, urban planners and public participation representatives, social organizations, as well as residents.